Shades of Gray : Writing the New American Multiracialism - McKibbin, Molly Littlewood (Book collections on Project MUSE., 2018)
"In Shades of Gray Molly Littlewood McKibbin offers a social and literary history of multiracialism in the twentieth-century United States"--